Using Nominal Group Technique to Develop a Consensus Derived Model for Peer Review of Teaching Across a Multi-school Faculty - Burrows, Tracy; Findlay, Naomi; Killen, Chloe; Dempsey, Shane; Hunter, Sharyn; Chiarelli, Pauline; Snodgrass, Suzanne (Journal of University Teaching and Learning Practice, 2011)
This paper describes the development of a peer review of teaching model for the Faculty of Health at the University of Newcastle, Australia. The process involved using the nominal group technique to engage Faculty academic staff to consider seven key decision points that informed the development of the peer review of teaching model. Use of the consensus based nominal group technique established collegial discussion and networking among participants, and has expanded the discussion within the Faculty about peer review of teaching. Although the academics come from a diverse multi-school and multi-program Faculty, there was high levels of consensus on the structure and process of the developed peer review of teaching model.